High seroprevalence after the second wave of SARS-COV2 respiratory infection in a small settlement on the northern coastal of Peru. - Toledo, Angie K. (2024)
Objective: a) to assess the seroprevalence of SARS-CoV-2 at the end of the second wave; b) to determine the distribution by age group and health determinants associated with seropositivity. Material and Methodology: A study performed in a Tumbes' settlement between December 2021–January 2022 sampled individuals over 2 years old from one to every four households. We collected finger-prick blood samples and conducted symptom surveys. Results: The adjusted seroprevalence after the second wave increased by twofold (50.15%, 95% CI[45.92–54.40]), compared with the first wave (24.82 %, 95%CI [22.49–27.25]). Females maintained a higher seroprevalence (53.89; 95% CI[48.48-59.23]) vs. 45.49; 95% CI [38.98-52.12], p=0.042) compared to males. Those under 18 years of age had the highest IgG seropositivity: the 12–17 age group during the second wave (85.14%) and the 2–11 age group (25.25%) during the first wave. Nasal congestion and cough were symptoms associated with seropositivity, unlike the first wave. Conclusions: The seroprevalence of COVID-19 increased by twofold compared to the initial wave in Tumbes region. Infrastructure constraints, restricted human resources, and supply limitations in healthcare facilities made the Peruvian health system collapse. The epidemiological surveillance network should incorporate mHealth tools for real-time notifiable disease information. Working alongside the community will let us improve interventions for preventing or controlling new pandemics.